Research Trends in Digital Financial Inclusion: A Bibliometric Analysis using VoSviewer - Ahiase, Godwin; Umar, Abdurrauf; M. Saeed, Abdulmalek Marwan; Rasuman, Mohammad Abedin; do Rego Tilman Suri, Epifania Rianti (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
Digital financial inclusion (DFI) aims to provide affordable and sustainable financial services to the financially excluded and underserved through cost-effective digital means. This quantitative bibliometric and descriptive research aims to conduct a bibliometric analysis of DFI using VOSviewer software. Data was collected based on the keyword "digital financial inclusion" from Google Scholar. From the results, in 2019 the number of DFI publications increased compared to 2018, indicating an increase in interest. The number remained stable in 2020 and 2021, but there was a significant spike in research interest in 2022. These findings are important for policymakers, researchers, and practitioners to determine the novelty and quantity of the data.